1980
DOI: 10.1021/jm00177a009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity correlations of rifamycins as inhibitors of viral RNA-directed DNA polymerase and mammalian .alpha. and .beta. DNA polymerases

Abstract: Twenty-two 3-substituted rifamycins were tested for inhibition of mammalian alpha and beta DNA polymerase and viral RNA-dependent DNA polymerase ("reverse transcriptase"). Quantitative structure--activity relationships (QSAR) were formulated for the three systems. Inhibition is linearly dependent on the partition coefficient and is highly favored by the presence of bulky hydrazones or oximes. None of these agents proved to be a selective or specific inhibitor of reverse transcriptase. A correlation in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In particular, the study by Wu et al (1980) demonstrated that increasing the lipophilicity of the compounds does not provide more specific inhibitors. In particular, the study by Wu et al (1980) demonstrated that increasing the lipophilicity of the compounds does not provide more specific inhibitors.…”
Section: H Friedman and S Spectermentioning
confidence: 99%
“…In particular, the study by Wu et al (1980) demonstrated that increasing the lipophilicity of the compounds does not provide more specific inhibitors. In particular, the study by Wu et al (1980) demonstrated that increasing the lipophilicity of the compounds does not provide more specific inhibitors.…”
Section: H Friedman and S Spectermentioning
confidence: 99%